Finitely Generated Simple Graphs - Türkmen, Burcu Nişancı; Karaca, Gülçin (Universitas Sanata Dharma, 2023)
In this paper, Kirchhoff, Hyper-Wiener, Randic, Szeged, Pi index calculations of finitely generated (cyclic) identity graphs on the samples were made and classification of some finitely generated (cyclic) groups was achieved with the help of graph theory.